DETEKSI FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN DENGAN FRAUD HEXAGON - Shabrina Isalati, Nadhiya; Taufik Azis, Mohammad; Hadiwibowo, Imam (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aim to examine and analyze the effect of the fraud hexagon factor as proxied by financial stability, ineffective monitoring, auditor change, director change, frequent number of CEO's picture and political connection on financial statement fraud in the food and beverage sub sector listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The population of this study amounted to 76 companies. 44 companies were selected as research samples based on purposive sampling, so there were 132 sample data. The data analysis method used is logistic regression analysis. The results show that financial stability and frequent number of CEO's picture have a positive effect on financial statement fraud, auditor change has a negative effect on financial statement fraud. Meanwhile, ineffective monitoring, director change and political connection have no effect on financial statement fraud.